OPTIMIZATION DESIGN OF WELDED METAL STRUCTURES BY MEANS OF SOLIDWORKS SIMULATION ON THE EXAMPLE OF WAREHOUSE RACKS - KHARZHEVSKYI, VIACHESLAV; BOZHEK, ROMAN; PIDHAICHUK, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper is dedicated to the problem of the optimization design of welded metal structures using the method of the finite element analysis, using the criteria of maximum von Mises stress for ductile materials and maximum displacement to ensure the stiffness of the model, that are implemented in SOLIDWORKS Simulation – Computer-Aided Engineering software. As shown in the paper on the example of strength calculation of a rack for a warehouse, when calculation model has welded metal parts with sheet metal, it has a number of peculiarities. In particular, the division of the parts of the model into the finite elements was carried out for the channel elements and for the rectangular pipes as finite elements of the type of “beam”, but sheet metal parts must be considered as finite elements of the type of “shell”, and the contact of metal sheets to beams must be considered as welded joints, using the contact type “bonded”. The load on the structure was simulated by placing two standard Euro pallets (1200x800) in the center on each shelf of the rack, and the load was simulated as “Gravity force”. According to the results of the strength calculations using SOLIDWORKS Simulation, which were obtained using the optimization techniques that are available in the engineering software, changes to the construction of the rack were proposed, which provided the required factor of safety. Therefore, the use of a proposed design will allow much more efficient usage of the warehouse area and will prevent critical rack overload.